Mapping Review Penerapan Artificial Intelligence pada Cyber Security untuk Meningkatkan Security Awareness - I Putu Agus Eka Pratama; I Made Oka Widyantara; Linawati; Nyoman Gunantara (Ikatan Ahli Informatika Indonesia, 2024)
The rapid development of information technology (IT), on the one hand, has the potential to increase the number of cyber attacks, so cyber security needs to be handled properly. As the weakest element, efforts are needed to increase cyber security awareness on the user side. Artificial intelligence (AI), which is increasingly developing and widely applied in various fields of life, has the potential to be used to increase security awareness in users. To study this further, a literature study, review, and mapping analysis were conducted from a number of references in order to obtain an overview of the potential and future research plans related to the use of AI in cyber security for security awareness along with providing recommendations. This study conducted a study and analysis using the mapping review method on 37 selected papers indexed by Google Scholar, referring to the NIST (National Institute of Standards and Technology) framework. The results of the mapping review show that the mapping of publications related to the application of AI to cyber security to increase security awareness is the most in 2024, with the most trends being education/training, and the most widely used AI method is deep learning. This study recommends education and deep learning as areas that can be taken for future research related to the application of AI to cyber security.